2021
DOI: 10.1016/j.ajhg.2020.11.015
|View full text |Cite
|
Sign up to set email alerts
|

SCUBE3 loss-of-function causes a recognizable recessive developmental disorder due to defective bone morphogenetic protein signaling

Abstract: Signal peptide-CUB-EGF domain-containing protein 3 (SCUBE3) is a member of a small family of multifunctional cell surface-anchored glycoproteins functioning as co-receptors for a variety of growth factors. Here we report that biallelic inactivating variants in SCUBE3 have pleiotropic consequences on development and cause a previously unrecognized syndromic disorder. Eighteen affected individuals from nine unrelated families showed a consistent phenotype characterized by reduced growth, skeletal anomalies, dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 57 publications
5
33
0
Order By: Relevance
“…The implication of SCUBE3 as a skeletal disease-causing gene was supported by our identification of mice homozygous for the Scube3 C301Y allele developing severe skeletal defects. In the course of this study, multiple patients were reported with recessive SCUBE3 mutations presenting with skeletal and non-skeletal manifestations similar to the index patient reported here (Lin et al, 2021). Using two independent experimental assays, we show that missense variants identified in our mouse model and the undiagnosed patient reported here, as well as other missense variants recently reported (Lin et al, 2021), abrogated the interaction between SCUBE3 and SCUBE1 and reduced transactivation of Smad signaling.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The implication of SCUBE3 as a skeletal disease-causing gene was supported by our identification of mice homozygous for the Scube3 C301Y allele developing severe skeletal defects. In the course of this study, multiple patients were reported with recessive SCUBE3 mutations presenting with skeletal and non-skeletal manifestations similar to the index patient reported here (Lin et al, 2021). Using two independent experimental assays, we show that missense variants identified in our mouse model and the undiagnosed patient reported here, as well as other missense variants recently reported (Lin et al, 2021), abrogated the interaction between SCUBE3 and SCUBE1 and reduced transactivation of Smad signaling.…”
Section: Discussionsupporting
confidence: 74%
“…(D) Schematic of the human SCUBE3 protein, including relative positions of annotated domains. Recently published variants identified in patients with skeletal disease (Lin et al, 2021) are shown in bold black. The human ortholog of the mouse ENU variant and the novel human variant reported here are shown in red.…”
Section: Radiographic Screen For Spine Deformitymentioning
confidence: 99%
See 3 more Smart Citations